The Challenges Faced by Novice Teachers of English for Medical Purposes (Emp): The Case of Saudi Arabia's Medical Colleges: NA - Eligindi, Hani Elgindi; Hoque, Mohammed Shamsul (International Journal of Language and Literary Studies, 2022)
The teachers of English for Medical Purposes (EMP) are faced with problems of lack of appropriate materials, professional support, low learner motivation and no provision of writing study module at medical colleges of Saudi Arabia. There is not enough study on these issues and researchers are quiet about addressing them. Understanding the new English for Medical Purposes teachers' challenges is of crucial importance to improve their performance and, accordingly, their students' performance. Thus, the main purpose of this study is to investigate the challenges of the new EMP teachers in teaching medical English via exploring the present situation analysis (PSA). This study follows a qualitative approach to conduct an investigation through rigorous interview with five EMP teachers (Ts) and three medical professors (MP) who are the deans of different medical colleges of Saudi Arabia. Data were entered through Atlas ti. Software to be sorted and analyzed for findings which were presented in figures and graphs. The study has found that new EMP teachers face difficulties, such as, adjustment of the English words in the medical context, pronunciation, and the meaning of the medical terminology. They also face challenges such as English used for medical procedures, daily routine in medical institutions, communication with medical staff and patients. But there is hardly any help available for the new EMP teachers to cope with this situation. Pedagogical issues, such as, the methodology of ESP is another area the EMP teachers find it difficult to tackle it. The findings call for steps to find solutions for these challenges to improve the performance of EMP teachers and their students.